Wybrane próby typologii informacyjnych organizacji sieciowych - Niestrój, Krzysztof (Selected Attempt of Information Network Organizations Typology, 2005)
The paper briefly presents three different classifications of information networks. First of them was presented by W. Appel, J. Gutenberg and R. Behr and introduce the terms of first and second level of virtual network. Second classification, proposed by N. Lethbridge, distinguishes six different types of information networks basing on the way and character of information flows. The last classification was presented by B. Gomes-Cesseres and is based on the common goal of the networks participants.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 123-129